Lokakarya Representasi Kalimat Sufistik Nisan Sultan Malik Al-Saleh dalam Mural untuk Penguatan Visual Budaya Dayah Manbaul Kota Jantho: Pengabdian - Setiawan, Indra; Saputra, Yulfa Haris; Husni, Teuku Muhammad; Sari, Dian Permata; At- Thariq, Ahmad Faza; farisyi, Salman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to represent the Sufi sentences engravedon the tombstone of Sultan Malik Al-Saleh in the form of a mural as a medium for strengthening visual culture in the Manbaul Dayah environment, Jantho City. The Sufi values ​​contained in the tombstone reflect the spiritual depth and local wisdom that are important to be passed on to the younger generation, especially the students at the dayah. Through a participatory workshop method involving the community service team and students, this activity was carried out in three main stages: (1) Dissemination related to visual arts in the realm of education, visual arts in Acehnese cultural history and mura art. (2) mural visual design and collaborative workshop process at the dayah. The results of this community service activity show that murals not only function as aesthetic elements, but also as educational media that can strengthen the understanding of cultural and spiritual values ​​in dayah education. This activity contributes to strengthening local cultural identity and increasing appreciation for the historical heritage